The Evaluation of New Marketing Strategy of Selected Home Appliances - Ghosh, Chinmoy (International Research Journal of Management, IT & Social Sciences, 2016)
The struggle for existence and growth is indeed very hard for firms in a competitive environment. As the environment changes their vision and objectives, structure, portfolio of business, market and competitive strategies Poke Strategy, includes the four ingredients such as Price, offers, brand, competitive marketing strategies.